Remote sensing and GIS for spatial analysis of surface water quality and soil pollution - Kreta, D.L.; Klymenko, V.I.; Anpilova, Ye.S. (Kyiv National University of Construction and Architecture, 2018)
The paper presents cartographic models for assessing the quality of soils and surface waters, scientific justification for improving existing monitoring, making operational management decisions for ecological security problems based on the use of modern means of Geographic Information Systems (GIS), methods of remote sensing of the Earth (remote sensing) from space, including through cartographic generalizations of data.